2021
DOI: 10.1302/1863-2548.15.210076
|View full text |Cite
|
Sign up to set email alerts
|

Histological and radiographic evaluation of three common tendon transfer techniques in an un-ossified bone porcine model: Implications for early anterior tibialis tendon transfers in children with clubfeet

Abstract: Purpose To compare the histological healing and radiographic effects of tendons transferred to ossified or unossified bone using different tendon fixation techniques Methods Nine new-born piglets underwent bilateral tendon transfers to either the ossified boney calcaneal body or unossified apophysis. The tendons were fixed using metallic suture anchors, sutures alone or a bone tunnel. At six weeks of age, calcanei were harvested, radiologically imaged and then prepared for histology. A semi-quantitative aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Methods using a metallic suture anchor, sutures alone or a bone tunnel were compared. They found that on histology, suture anchor fixation demonstrated the worst healing in both the ossified and unossified samples with minor alterations in apophyseal ossification seen with all methods, with the most significant changes observed in the metallic suture anchor cohort [13]. The youngest patient in our cohort was 3.4 years.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Methods using a metallic suture anchor, sutures alone or a bone tunnel were compared. They found that on histology, suture anchor fixation demonstrated the worst healing in both the ossified and unossified samples with minor alterations in apophyseal ossification seen with all methods, with the most significant changes observed in the metallic suture anchor cohort [13]. The youngest patient in our cohort was 3.4 years.…”
Section: Discussionmentioning
confidence: 91%
“…There has been limited investigation into the comparative efficacy of the different methods of tibialis anterior docking in children. Halanski et al [18] and Korth et al [13] have published similar work regarding the effect of the transfer on subsequent bone growth and the different pullout strengths of three techniques in unossified porcine bone [13,15]. Halanski et al [18] drilled a tunnel using an 18 gauge needle in the bony or cartilaginous portion of the calcaneus of 25 piglets.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations